Medical histories of Belgium New narratives on health, care and citizenship in the nineteenth and twentieth centuries - Vandendriessche, Joris; Majerus, Benoit (Manchester University Press, 2021)
This edited volume offers the first comprehensive historical overview of the Belgian medical field in the nineteenth and twentieth centuries. Its chapters develop narratives that go beyond traditional representations of medicine in national overviews, which have focused mostly on stateprofession interactions. Instead, the chapters bring more complex histories of health, care and citizenship. These new histories explore the relation between medicine and a variety of sociopolitical and cultural views and realities, treating themes such as gender, religion, disability, media, colonialism, education and social activism. The novelty of the book lies in its thorough attention to the (too often little studied) second half of the twentieth century and to the multiplicity of actors, places and media involved in the medical field. In assembling a variety of new scholarship, the book also makes a contribution to 'decentring' the European historiography of medicine by adding the perspective of a particular country Belgium to the literature.